Real-time bridge scour monitoring system by using capacitor sensor - Motakabber, S. M. A.; Ibrahimy, Muhammad Ibn; Alam, A. H. M. Zahirul (2013)
Scour is the erosion of stream bed or bank material from bridge foundations due to flowing of water. Data logging from sens or and electronic communication systems can mo nitor scour in real - time to ensu re the integrity of bridge structure. A number of parameters are associated with scour, thus different types of sensor are required to measure the individual affecting factor. A simple capacitive type direct scour sensor system is proposed and validated by simulation. The result shows that any change of the river bed dielectric property is a direct indication of scour. Due to simple capacitive structure of the sensor system , it is highly robust and easy to implement. The system can easily be implement ed wit h an existing bridge structure . A wireless telemetry system can be used to send the real - time data from the proposed sensor to a desktop computer at the monitoring lab